2006
DOI: 10.1089/apc.2006.20.326
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a "Treatment Success": What Helps and What Hinders Patients from Achieving and Sustaining Undetectable Viral Loads

Abstract: Highly active antiretroviral therapy (HAART) adherence research has focused predominantly on individuals with less than optimal clinical outcomes; therefore, little is known about the experiences of individuals who sustain undetectable viral loads. The present study used a qualitative method to explore how individuals who have sustained undetectable viral loads account for their success, and to identify challenges, as well as possible needs, for continued success. Participants were 20 patients at an outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…For instance, support can be seen as an encouragement to engage in health behaviors. Conversely, the lack of support or isolation can become a barrier to health behavior adherence or adherence more generally, as was reported in a qualitative study of cancer survivors 27 and HIV patients 28 . Social support is also related to broader types of health behavior, including fruit and vegetable consumption, exercising 29 , and smoking cessation 30 .…”
Section: Focus On Potential Pathwaysmentioning
confidence: 98%
“…For instance, support can be seen as an encouragement to engage in health behaviors. Conversely, the lack of support or isolation can become a barrier to health behavior adherence or adherence more generally, as was reported in a qualitative study of cancer survivors 27 and HIV patients 28 . Social support is also related to broader types of health behavior, including fruit and vegetable consumption, exercising 29 , and smoking cessation 30 .…”
Section: Focus On Potential Pathwaysmentioning
confidence: 98%
“…Depression has been identified as one of the most important mental health-related barriers to ART adherence (Alfonso, Geller, Bermbach, Drummond, & Montaner, 2006). The symptom picture for depression includes low motivation, poor concentration, sleep disturbance, psychomotor retardation, fatigue or loss of energy, and feelings of worthlessness (American Psychiatric Association [APA], 2000), all of which have very clear implications for clinic attendance and medication adherence.…”
Section: Depressionmentioning
confidence: 99%
“…It has therefore been suggested that when patients are initiated on ART, they should be routinely screened for psychiatric conditions (Campos, Guimara˜es, & Remien, 2008). These authors reason that screening may permit the detection of common mental health problems, the treatment of which may increase the likelihood of adherence (Alfonso et al, 2006). Yet, the recommendation of screening is not without controversy.…”
Section: Preventative Measuresmentioning
confidence: 99%
“…2,3 While the new hope from the ARVs is unprecedented global development, the requirement of indefinite adherence to the treatment demands the clients a significant modification of life style and retention in lifelong intensive treatment. 4 Meeting these requirements at times is a huge challenge for patients. Factors related to socioeconomic status, health care systems, therapy itself, and the patient pose hindrance to ARV adherence.…”
Section: Introductionmentioning
confidence: 99%